Hazardous, harmful, and dependent alcohol use in healthcare professionals: a systematic review and meta-analysis - Halsall, Lauren; Irizar, Patricia; Burton, Sam; Waring, Sara; Giles, Susan; Goodwin, Laura; Jones, Andrew (Frontiers in Public Health, 2023)
Background: Healthcare professionals work in high-pressured and demanding environments, which has been linked to the use of alcohol as a coping strategy. This international review aimed (i) to determine the pooled prevalence of hazardous, harmful, dependent, and frequent binge drinking in healthcare professionals, and (ii) to explore factors associated with variation in these outcomes. Methods: Scopus, MEDLINE, and PsycINFO were searched from 2003 to 17 th November 2022, for studies reporting a prevalence estimate for any outcome among healthcare professionals. Randomeffects meta-analyses determined pooled prevalence estimates. Sub-group analyses were conducted, stratifying the meta-analyses by pandemic period vs pre-pandemic period. Meta-regressions explored factors that were associated with variation in the outcomes. PROSPERO (CRD42020173119). Results: After screening 9,108 records, 64 studies were identified as eligible. The pooled prevalence was 19.98% [95% Confidence Intervals [CI]: 16.05% -24.23%] for hazardous alcohol use (K = 52), 3.17% [95% CI: 0.95% -6.58%] for harmful drinking (K = 8), 14.59% [95% CI: 7.16% -25.05%] for dependent drinking (K = 7), and 17.71% [95% CI: 8.34% -29.63%] for frequent binge drinking (K = 11). The prevalence of hazardous drinking was significantly greater during the pandemic (28.19%) compared with pre-pandemic estimates (17.94%). Studies including all hospital staff (32.04%) showed higher prevalence estimates for hazardous drinking compared with studies of doctors (16.78%) and nurses (27.02%). Conclusions: Approximately one fifth of healthcare professionals drink to hazardous levels, with higher prevalence estimates observed during the COVID-19 pandemic. It may be that healthcare professionals used alcohol to cope with the additional trauma and stressors. Further research is needed to investigate whether this is sustained in the post-pandemic period.